1965
DOI: 10.2307/779810
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliography of Early Secular American Music

Abstract: The majoritj^o f the pieces show words and tune only, but several are set for two, three, and four voices. The arrangement generally is such as to allow an accompaniment on the pianoforte unisono with the voice or voices. In the two-part songs the right hand plays the tune and the left a simple bass, like in many other collections of the time, but with this difference that the basses are not figured.In some instances short preludes or postludes are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple mounted portraits have been identified, along with a copy where the illustration was inked onto the sheet (1a). Upton has suggested that a more widely available variant, which features a mounted portrait of Adams, was Carr's initial product (1b), 42 but it seems more likely that Figure 1a represents Carr's original design. In another surviving copy a mounted portrait was removed, leaving a wax residue (1c).…”
Section: The Politics Of "Hail Columbia"mentioning
confidence: 99%
“…Multiple mounted portraits have been identified, along with a copy where the illustration was inked onto the sheet (1a). Upton has suggested that a more widely available variant, which features a mounted portrait of Adams, was Carr's initial product (1b), 42 but it seems more likely that Figure 1a represents Carr's original design. In another surviving copy a mounted portrait was removed, leaving a wax residue (1c).…”
Section: The Politics Of "Hail Columbia"mentioning
confidence: 99%